Sharia Financial Institutions : Basic Concepts and Implementation in Society - Muhammad Hanafi (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
Sharia Financial Institutions (LKS) have emerged as an important alternative in the global financial system, offering solutions for people who want to make transactions in accordance with Islamic principles. This article examines the basic concepts underlying sharia financial institutions, including the prohibition of usury, gharar, and investment in the halal sector. By using a qualitative approach and literature study, this research also analyzes how LKS is implemented in society today, as well as its impact on economic welfare. In addition, this article highlights the challenges faced by Islamic financial institutions, such as limited public understanding and regulations that are not yet fully supportive. It was found that although LKS shows significant growth and positive contribution in increasing financial inclusion, challenges such as education and technology still need to be addressed. Through a better understanding of the concept and implementation of sharia financial institutions, it is hoped that this article can provide insight for stakeholders in optimizing the role of these institutions in a more just and sustainable economy. In this way, Islamic financial institutions are expected to make a greater contribution in creating a financial system that is more ethical and responsive to community needs. Keywords : sharia principles, LKS structure, halal investment